Double-Valued Neutrosophic Offset for Enhancing Humanistic Competence: An Effectiveness Study of Humanities Instruction in Vocational College Students - Lingling Lin (Neutrosophic Sets and Systems)
In the context of increasingly skills-oriented education, vocational colleges face the challenge of producing technically competent graduates who are also ethically grounded, culturally aware, and socially responsible. This study examines the effectiveness of humanities instruction in fostering humanistic competence among vocational college students. Six key evaluation criteria—critical thinking, ethical awareness, communication skills, cultural understanding, interpersonal abilities, and real-world applicability—are used to assess six distinct instructional approaches through a neutrosophic set framework. Data was gathered from student surveys, faculty interviews, and classroom observations across multiple institutions. This study uses the neutrosophic set framework to overcome uncertainty information. We use the Double-Valued Neutrosophic Offset to evaluate the criteria and alternatives. The results demonstrate that interdisciplinary project-based learning (PBL) and courses emphasizing ethics and civic responsibility most effectively promote holistic student development. The findings underline the value of humanities in shaping not only employable but also reflective and socially engaged graduates, offering evidence-based recommendations for curriculum planners in vocational education settings.